A new species of planthopper belonging to the genus Oecleus Stål, 1862 (Hemiptera: Fulgoroidea: Cixiidae) from coconut palm (Cocos nucifera L) in Jamaica - Myrie, Wayne; Helmick, Ericka E.; Bartlett, Charles R.; Bertaccini, Assunta; Bahder, Brian W. (Zootaxa, 2019)
A new species of cixiid planthopper (Hemiptera: Fulgoroidea) in the genus Oecleus Stål, Oecleus mackaspringi sp. n., is described from Spring Garden, Jamaica. This new taxon is associated with coconut palm (Cocos nucifera L.) and was found while surveying palm plots with active cases of lethal yellowing (LY). This is the first report of the genus Oecleus from Jamaica. Sequence data for the COI gene and 18S gene are also provided.